Recurrent genomic rearrangements in primary testicular lymphoma. Issue 2 (26th March 2015) - Twa, David DW; Mottok, Anja; Chan, Fong Chun; Ben‐Neriah, Susana; Woolcock, Bruce W; Tan, King L; Mungall, Andrew J; McDonald, Helen; Zhao, Yongjun; Lim, Raymond S; Nelson, Brad H; Milne, Katy; et al.
Abstract Primary testicular diffuse large B cell lymphoma (PTL) is an aggressive malignancy that occurs in the immune‐privileged anatomical site of the testis. We have previously shown that structural genomic rearrangements involving the MHC class II transactivator CIITA and programmed death ligands (PDLs) 1 and 2 are frequent across multiple B cell lymphoma entities. Specifically in PTL, we found rearrangements in the PDL locus by fluorescence in situ hybridization (FISH). However, breakpoint anatomy and rearrangement partners were undetermined, while CIITA rearrangements had not been reported previously in PTL. Here, we performed bacterial artificial chromosome capture sequencing on three archival, formalin‐fixed, paraffin‐embedded tissue biopsies, interrogating 20 known rearrangement hotspots in B cell lymphomas. We report novel CIITA, FOXP1 and PDL rearrangements involving IGHG4, FLJ45248, RFX3, SMARCA2 and SNX29. Moreover, we present immunohistochemistry data supporting the association between PDL rearrangements and increased protein expression. Finally, using FISH, we show that CIITA (8/82; 10%) and FOXP1 (5/74; 7%) rearrangements are recurrent in PTL. In summary, we describe rearrangement frequencies and novel rearrangement partners of the CIITA, FOXP1 and PDL loci at base‐pair resolution in a rare, aggressive lymphoma. Our data suggest immune‐checkpoint inhibitor therapy as a promising intervention for PTL patients harbouring PDL rearrangements. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.